Russian intelligence files on Asia. (Leiden, The Netherlands)
1 mikrofilm makarası (584 poz)
Keywords: Geographical, military topography and statistical material : Districts, provinces, and other large administrative entities : Manchuria, Mongolia, Eastern Turkestan (Xinjiang), Tibet. Cities and fortresses.